A replacement name for Acrapex albicostata Hampson, 1916 (Lepidoptera: Noctuidae) - de Prins, Willy (Zootaxa, 2021)
In 1905, O. B. Lower described Sesamia albicostata from Australia, based on one male specimen taken at Ocean Grange, near Sale, Victoria in January (Lower 1905: 175). Apart from the bibliographical records in the series Zoological Record (Sharp 1906: 262) and Archiv für Naturgeschichte (Lucas 1910: 613), the name Sesamia albicostata occurred only in two other subsequent publications. G. F. Hampson (1910: 327) repeated the short description of Lower without further comments, though he had seen the type specimen which was at that time preserved in the private collection of Lower. He depicted the specimen on plate 144 in fig. 21 [https://www.biodiversitylibrary.org/page/32600328] (Fig. 1).